Boosting the Rebustness of Controller Area Networks: CANcentrate and ReCANcentrate. - Barranco, Manuel; Proenza, Julián; Almeida, Luís (Computer (00189162), 2009)
The article presents research into star architectures which are based upon the Controller Area Network (CAN) protocol. The goal of improving the error containment and fault tolerance capabilities of the CAN protocol for general distributed embedded systems and applications of a safety-critical nature is noted. The superiority of star topologies over bus topologies for error containment is also mentioned, noting that star topologies tend to allow for the creation of more robust communication systems than lower-cost bus topologies.